The stone cold age - Brown, Jeffrey, 1975- (Brown, Jeffrey, 1975- Lucy & Andy Neanderthal (Series), 2017)
When their cave becomes overcrowded with humans, Neanderthal siblings Lucy and Andy start pulling pranks to make some room.